Penerapan Google Data Studio dalam Pembuatan Dashboard Analisis Daya Terima Menu Makanan Instalasi Gizi di Rumah Sakit Gigi dan Mulut Pendidikan Universitas X - Mirayanti Ahmad; Ma’rifat Istiqa Mukty; Rini Jusriani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Nutrition services in hospitals are an essential component in supporting the success of patient care. One of the key indicators of nutrition service quality is the menu acceptability, which refers to the level of patients’ preference and consumption of the meals served. Traditionally, the reporting of menu acceptability data has been performed manually using Microsoft Excel, which is time-consuming, prone to data entry errors, and less effective for rapid analysis and decision-making. This study aims to describe the application of Google Data Studio (GDS) in presenting food menu acceptability data visually and interactively in hospitals. The research uses a quantitative descriptive approach through observation and survey of nutritional personnel and processing of patients' food acceptability data. The results of the study show that the use of GDS simplifies the reporting process, increases time efficiency, and makes it easier to interpret data compared to manual methods using Excel. Respoden assessed that GDS helps present data in an informative and interactive manner, thereby supporting the data-driven decision-making process at the Nutrition Installation of the Dental and Oral Hospital of Hasanuddin University. It can be concluded that Google Data Studio has been shown to improve reporting efficiency and make it easier to visualize food acceptance data in hospitals. This system not only improves the efficiency and accuracy of reporting, but also strengthens evidence-based nutrition management in support of the hospital's digital transformation.